Mapping the Supply Chain System of the Tolaki Coffee Industry in South Konawe Regency - Lamatungga, Mansyar; Nuryadi, Ahmad Muhlis; Nur, Muhammad (Bincang Sains dan Teknologi, 2025)
The coffee agribusiness sector in South Konawe Regency has shown gradual growth with the emergence of a regionally distinctive coffee processing industry known as Tolaki Coffee. The name Tolaki Coffee is derived from the Tolaki ethnic group, the largest indigenous community in Southeast Sulawesi Province. However, since its establishment in 2016, the Tolaki Coffee industry has not demonstrated significant development compared to other well-established Indonesian specialty coffees, such as Toraja Coffee in South Sulawesi and Aceh Coffee in Aceh Province. Nevertheless, the existence of the Tolaki Coffee industry is expected to generate economic benefits for local coffee farmers, particularly through improved farm-gate prices and income enhancement. This condition provides the rationale for conducting an analysis aimed at designing a development model for the Tolaki Coffee processing industry using a supply chain approach to increase industry stakeholders’ income while strengthening farmer empowerment. This study aims to: (1) identify the supply chain system of Tolaki Coffee, and (2) analyze the performance of the Tolaki Coffee supply chain in South Konawe Regency. The research was conducted in three stages. The first stage involved analyzing the supply chain structure using quantitative descriptive analysis, followed by an assessment of supply chain efficiency using the farmer’s share analysis. The results indicate that: (1) the Tolaki Coffee supply chain system in South Konawe Regency consists of two marketing channels, namely Farmer – Collector Trader – Anoa Coffee Industry – Retailer – Consumer and Farmer – Anoa Coffee Industry – Retailer – Consumer, with processed products in the form of ground coffee and ready-to-grind coffee beans; and (2) the most efficient supply chain performance is observed in the Farmer – Anoa Coffee Industry – Retailer – Consumer channel for ground coffee products.